The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1016/s1010-7940(00)00443-7
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic congenital oesophageal cyst infiltrating the lung: an unusual complication

Abstract: An asymptomatic 14-year-old boy presented with minor chest trauma. Chest X-ray showed opacity in the upper zone of the left lung. Further investigations with magnetic resonance imaging showed it to be a posterior mediastinal mass with a fistula to the lung, along with cystic changes in the left upper lobe of lung. Left upper lobectomy with excision of the mass was performed. Histological examination later showed an oesophageal duplication cyst with a fistula to the left upper lobe of the lung. We present this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…In humans, upper oesophageal cysts usually lead to respiratory distress due to tracheobronchial compression, while middle and lower cysts can lead to gastrointestinal disturbances, such as dysphagia, regurgitation, vomiting and cardiovascular and respiratory symptoms, including arrhythmias and respiratory distress (Sundaramoorthi et al 2000;Carachi and Azmy 2002). Nonetheless, about 35% of the patients with middle or lower oesophageal cysts are asymptomatic, and, in our patient, only gastrointestinal symptoms were reported (Sundaramoorthi et al 2000;Jan et al 2016).…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…In humans, upper oesophageal cysts usually lead to respiratory distress due to tracheobronchial compression, while middle and lower cysts can lead to gastrointestinal disturbances, such as dysphagia, regurgitation, vomiting and cardiovascular and respiratory symptoms, including arrhythmias and respiratory distress (Sundaramoorthi et al 2000;Carachi and Azmy 2002). Nonetheless, about 35% of the patients with middle or lower oesophageal cysts are asymptomatic, and, in our patient, only gastrointestinal symptoms were reported (Sundaramoorthi et al 2000;Jan et al 2016).…”
Section: Discussionmentioning
confidence: 50%
“…A cut section revealed that the cyst contained abundant, viscous and yellow material which was partly adherent to the cystic wall https://doi.org/10.17221/113/2017-VETMED as a consequence of enlargement of the structure due to inflammation or haemorrhaging of the cyst (Sundaramoorthi et al 2000;Carachi and Azmy 2002;Martin et al 2007). In humans, upper oesophageal cysts usually lead to respiratory distress due to tracheobronchial compression, while middle and lower cysts can lead to gastrointestinal disturbances, such as dysphagia, regurgitation, vomiting and cardiovascular and respiratory symptoms, including arrhythmias and respiratory distress (Sundaramoorthi et al 2000;Carachi and Azmy 2002). Nonetheless, about 35% of the patients with middle or lower oesophageal cysts are asymptomatic, and, in our patient, only gastrointestinal symptoms were reported (Sundaramoorthi et al 2000;Jan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations